(untitled) (Acta Entomologica Serbica, 2011)
Genus Geocoris is represented in Serbia by nine species: Geocoris (Geocoris) arenarius (Jakovlev), Geocoris (Geocoris) ater (Fabricius), Geocoris (Geocoris) dispar (Waga), Geocoris (Geocoris) grylloides Linnaeus, Geocoris (Geocoris) lapponicus (Zetterstedt), Geocoris (Geocoris) lineola (Rambur), Geocoris (Geocoris) megacephalus (Rossi), Geocoris (Geocoris) pallidipennis (Costa) and Geocoris (Piocoris) erythrocephalus (Lepeletier & Serville). Geocoris (Geocoris) pallidipennis (Costa) is a new species for the fauna of Serbia.